2020
DOI: 10.7717/peerj.10410
|View full text |Cite
|
Sign up to set email alerts
|

Partial revision of the neustonic genusScapholeberisSchoedler, 1858 (Crustacea: Cladocera): decoding of the barcoding results

Abstract: Water fleas (Crustacea: Cladocera) are among the most intensively studied freshwater invertebrates. However, ecologically important daphniids that live on the surface layer (neuston) remain taxonomically confused. Here we attempt to reconcile genetic and morphological information for the neustonic genus Scapholeberis Schoedler, 1858 (Cladocera: Daphniidae) and present the first revision of the Scapholeberis kingii species group. We analyzed new and existing mitochondrial DNA sequences (сytochrome C oxidase sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 72 publications
0
9
0
Order By: Relevance
“…Species D. (D.) pulicaria is widespread in Eurasia and other continents; however, genetic studies have revealed [Crease et al, 2012] that this taxon is represented by a group of species that require detailed taxonomic revision. Scapholeberis microcephala is common in Scandinavia and European countries in the northwestern and central parts of European Russia up to the White Sea in the north [Garibian et al, 2020]. It is notable that the populations in Alaska and Sakhalin belong to another undescribed taxon [Taylor et al, 2020], our populations most probably also belong to it.…”
Section: Resultsmentioning
confidence: 74%
“…Species D. (D.) pulicaria is widespread in Eurasia and other continents; however, genetic studies have revealed [Crease et al, 2012] that this taxon is represented by a group of species that require detailed taxonomic revision. Scapholeberis microcephala is common in Scandinavia and European countries in the northwestern and central parts of European Russia up to the White Sea in the north [Garibian et al, 2020]. It is notable that the populations in Alaska and Sakhalin belong to another undescribed taxon [Taylor et al, 2020], our populations most probably also belong to it.…”
Section: Resultsmentioning
confidence: 74%
“…Subsequent revisions could improve our ideas on exact biogeographic status of the taxa belonging to WS. However, in general, more detailed study usually leads to acceptance of a higher level of endemism as compared to a non-revised state [10,96]. The chance that further studies will demonstrate a significantly high representation of Boreal taxa on Jeju Island, compared to the present, is minimal.…”
Section: Notes On Faunistic Structurementioning
confidence: 97%
“…It has been reported that monophyly with a short branch length can be used to determine the specimen's taxonomic status within a single clade (Xu et al 2015;Kusbiyanto et al 2020). Previous studies also used these parameters during species delineation based on molecular barcoding (Bekker et al 2016;Aguilar et al 2017;Nuryanto et al 2017;Lipinskaya et al 2018;Garibian et al 2020).…”
Section: Taxonomic Status Of Crustacean Larvaementioning
confidence: 99%